Acceptance and consumption of honeybees (Apis mellifera L.) for local pollen Paste and sugar syrup added to powder of some medicinal plants - AL-Jamali, Nassir Abdulsahib; Badgat, Hassanein M. (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted during June 2017 in the researcher's apiaries which located at the village of Albo Hwemid / AlHusseiniya - Karbala - Iraq, to evaluate the addition of some medicinal plants to increase or stimulate honey bees to increase the consumption of sugar syrup and local pollen grains paste. The anise, wormwood, cinnamon and saffron herbs were used which added to above foods. The results revealed that the addition of both anise and wormwood to the sugar syrup gave best attraction to honey bee, consumption average reached to 415 and 400 ml / colony respectively. But the wormwood which added to the local pollen grain paste gave high consumption average reached to 18.33 g / colony.